Pengaruh Pemberian Calistung terhadap Psikis Anak Usia - Hayani Wulandari; Annisa Aulia Rachma (Journal on Education, 2024)
The ability of early childhood to master calistung is a proud achievement for parents and makes a benchmark for success in educating children. This arises from the demands of lessons at the next level of education and the comparison of children who have brilliant abilities in calistung. So it is not uncommon for parents to force early childhood to learn calistung by not paying attention to the stages of child development that can affect children's mental intelligence which includes all psychic elements and actions performed or psychomotor and psychophysical. This research uses a qualitative approach with a literature study method in analyzing existing data and poured in the form of descriptive writing with the subject of reading, writing and counting skills (calistung) in early childhood. The results of the study provide an understanding to parents and teachers of the impact caused by giving calistung to children due to compulsion and demands that do not pay attention to the psychological development of children. This makes one of the bases for parents and teachers to pay attention to child development in the calistung learning process by not demanding results in calistung skills, and how to apply fun calistung to early childhood.